Determinants of Debt Structure in Japanese Corporates - Chen, Ee-Ann (2014)
This is the first paper to provide evidence on the determinants of debt structure of publicly listed firms in Japan. Our data provides a breakdown of debt into bank debt comprised of revolving credit and term loans, public debt composed of commercial paper, senior bonds and subordinated bonds and the remaining components consisting of capital leases and other debt. We demonstrate that debt composition varies according to access to public debt markets, credit market conditions and firm level characteristics. We first show that rated firms tend to have more public debt and less bank debt than non-rated firms. Furthermore, during periods of credit tightening, the role of credit ratings becomes more significant in terms of driving debt structure. We then show that rated firms have on average a more diversified debt structure than non-rated firms. Finally, we demonstrate that large firms with high liquidity and a large proportion of tangible assets on average have a higher proportion of public debt while small firms with low profitability, low liquidity and high equity volatility on average employ more private debt.